The Inventory of Macroalgae in The Rengge Beach, Pari Island, Thousand Islands, Jakarta - Pinta Omas Pasaribu; Rizal Koen Asharo; Nailul Rahmi Aulya; Novia Lis Cahyati; Nurul Assyifa Wardana; Ade La Yusup; Farhana Faridah Achmad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Pari Island is one of the islands among the Thousand Islands group, about 46.32 km from the center of Jakarta with a total area of 310,000 km2 has high biodiversity, one of which is from the macroalgae group. Although macroalgae are a source of high biodiversity, the utilization of macroalgae is still very minimal to do because of the lack of education in the community about the types and benefits of macroalgae found in waters. This study aims to determine the diversity of macroalgae in Rengge Beach, Pari Island, Kepulauan Seribu, Jakarta so that later the community can find out more information about the types, characteristics, and potential utilization of macroalgae. The research was conducted in December 2022 using the benthic belt transect method with a total of 5 stations, carried out by drawing a line from the shoreline inland with a transect length of 100 m and a width of 10 m (5 m to the right and left sides), a monitoring area of 1 km² (10x100 m) between stations. Samples were taken and identified to the species level at the Plant Structure and Development Laboratory, Biology study program, Jakarta State University, Jakarta. Observations include several characteristics both morphologically and anatomically. The results showed that there were five species of macroalgae that could be identified, namely Halimeda sp, Gracilaria sp, Turbinaria sp, Padina sp, and Sargassum sp, therefore it can be concluded that there are only five genera of macroalgae in this place. This research needs more development that can provide more benefits, one of which is to develop the research area and further identify the types of macroalgae obtained to find out more specific information about the potential of macroalgae.